Extremophilic Polysaccharide for Biosynthesis and Passivation of Gold Nanoparticles and Photothermal Ablation of Cancer Cells. (28th July 2014) - Raveendran, Sreejith; Chauhan, Neha; Palaninathan, Vivekanandan; Nagaoka, Yutaka; Yoshida, Yasuhiko; Maekawa, Toru; Kumar, D. Sakthi
<x xml:space="preserve">Abstract</x> Extremophiles are the group of organisms that are far overlooked for exploring novel biomaterials in the field of material science and bionanotechnology. Extremophilic bacterial‐sulfated exopolysaccharide, mauran (MR), is employed for the bioreduction and passivation of gold nanoparticles (AuNps) to enhance the biocompatibility of AuNps and used for photothermal ablation of cancer cells. Here, various concentrations of MR solution are tested for the reduction of HAuCl4 solution in the presence as well as in the absence of an external reducing agent, to produce mauran‐gold nanoparticles (MRAu Nps). These biocompatible nanocomposites are treated with cancer cell lines under in vitro conditions and NIR irradiated for complete ablation. MRAu Nps‐treated cancer cells on immediate exposure to infrared radiation from a femtosecond pulse laser of operating wavelength 800 nm are subjected to hyperthermia causing cell death. Biocompatible MR stabilization could fairly reduce the cytotoxicity caused by bare AuNps during biomedical applications. Application of a biocompatible polysaccharide from extremophilic bacterial origin for reduction and passivation of AuNps and used for a biomedical purpose is known to be first of its kind in bionanofusion studies.